Che‐1‐induced inhibition of mTOR pathway enables stress‐induced autophagy. (14th March 2015) - Desantis, Agata; Bruno, Tiziana; Catena, Valeria; De Nicola, Francesca; Goeman, Frauke; Iezzi, Simona; Sorino, Cristina; Ponzoni, Maurilio; Bossi, Gianluca; Federico, Vincenzo; La Rosa, Francesca; Ricciardi, Maria Rosaria; et al.
Abstract Mammalian target of rapamycin (mTOR) is a key protein kinase that regulates cell growth, metabolism, and autophagy to maintain cellular homeostasis. Its activity is inhibited by adverse conditions, including nutrient limitation, hypoxia, and DNA damage. In this study, we demonstrate that Che‐1, a RNA polymerase II‐binding protein activated by the DNA damage response, inhibits mTOR activity in response to stress conditions. We found that, under stress, Che‐1 induces the expression of two important mTOR inhibitors, Redd1 and Deptor, and that this activity is required for sustaining stress‐induced autophagy. Strikingly, Che‐1 expression correlates with the progression of multiple myeloma and is required for cell growth and survival, a malignancy characterized by high autophagy response.